Measuring Competence? Exploring Firm Effects in Pharmaceutical Research - Henderson, Rebecca; Cockburn, Iain (Strategic Management Journal, 1994)
Renewed interest in the resource-based theory of the firm has focused attention on the role of heterogeneous organizational ‘competence’ in competition. This paper attempts to measure the importance of these effects in the context of pharmaceutical research. We distinguish between ‘component’ and ‘architectural’ competence, and using internal firm data at the program level from 10 major pharmaceutical companies show that together the two forms of competence appear to explain a significant fraction of the variance in research productivity across firms. Our results raise some intriguing questions about the nature of competencies and the ways in which they diffuse over time.